Characterization of Recycled Aggregates from Building Demolition Waste for Use in Road Infrastructures - Majid Ahmadpour; Davood Akbarimehr; Mohammad Rahai; Ali Momeni (Infrastructures, 2025)
In light of rising environmental concerns, the rapid industrial recycling of building demolition waste material (BDWM) is now capable of supporting sustainable development in metropolitan regions. From this perspective, the current study investigated the geotechnical properties and applications of BDWMs as substitutes for natural materials (NMs) in road engineering infrastructures. For this purpose, the physical and geotechnical characteristics of both types of materials were initially examined, and then compared using laboratory-scale material comprehensive assessments such as sieve analysis (SA), the flakiness index (FI), the specific gravity test (Gs), the Los Angeles abrasion test (LAAT), Atterberg limits (AL), the water absorption test (WAT), the California bearing ratio (CBR), the direct shear test (DST), and the Proctor soil compaction test (PSCT). The BDWMs were collected from two locations in Iran. According to the results, the collected samples consisted of concrete, bricks, mortar, tile materials, and others. The CBR values for the waste material from the two sites were 69 and 73%, respectively. Furthermore, the optimum water content (OWC) and maximum dry unit weight (MDD) from the two sites were reported as 9.3 and 9.9% and 20.8 and 21 kN/m3, respectively, and the hydrogen potential (pH) as 9 and 10. The shear strength and CBR values indicated that the BDWM had a suitable strength compared to the NM. In terms of road infrastructure applications, the shear strengths were adequate for the analysis of common sub-base materials used in filling and road construction. Furthermore, the study’s findings revealed that BDWMs were suitable replacements for the NM used in road engineering operations and could make a significant contribution to sustainable development.